« Leprous literature » : le modèle de la transmission contesté par les théories esthétiques d’Oscar Wilde - Carole Delhorme (Cahiers Victoriens et Edouardiens)
In the late nineteenth century, the English press often used the metaphor of contamination to refer to publications deemed immoral or obscene. It conveyed the idea that just like a contagious disease, the immorality of a book could be transmitted to the reader and could corrupt them. The critical reception of the first publication of The Picture of Dorian Gray in 1890 was no exception, as is shown by an article published in the Daily Chronicle: ‘[It] is a tale spawned from the leprous literature of the French Decadents—a poisonous book, the atmosphere of which is heavy with the mephitic odour of moral and spiritual putrefaction’. (quoted by Aquien 19). This lexicon echoed the legal standards that defined the limits to freedom of expression. Indeed, according to the leading case R v Hicklin (1868), which set a precedent for almost a century, a publication was defined as obscene if it had a ‘tendency... to deprave and corrupt those whose minds are open to such immoral influences’, regardless of its literary merit. The morality of a work, as well as the legal and moral responsibility of the artist, could therefore be judged based on the influence that the work could exert on the reader. This paper examines the extent to which Oscar Wilde’s aesthetic theories, as articulated in his critical works collected in Intentions, respond to and challenge this evaluative framework. The Preface to The Picture of Dorian Gray, which proclaims the doctrine of art for art’s sake and the separation of the realm of art from that of action, has been seen as a manifesto against censorship, whether it be legal or extra-legal. The aim of this paper is to extend the analysis to other aspects of Wilde’s aesthetic theories. For instance, by relying on the subjectivity and arbitrariness of artistic reception, the theory of creative criticism makes the reader accountable for the interpretation of the work, so as to absolve the author from any responsibility.